TESTING ORGANIZATIONAL COMMITMENT ON EMPLOYEE SATISFACTION: SURVEY ON SUB-DISTRICT OFFICES IN BANDUNG - Kadir Kadir; Aan Hardiyana; Rd. Okky Satria (Jurnal Computech & Bisnis (e-Journal), 2021)
This study departs from the existence of problems in employee job satisfaction, which indicate the non-optimal work commitment of employees. Instead, this study aims to determine the magnitude of the effect of organizational commitment components on employee job satisfaction—this research conduct at two sub-district offices in Bandung. To determine the magnitude of the influence of the organizational commitment component on employee job satisfaction, the researcher used a quantitative approach by testing a sample of 57 employees. The data analysis technique used multiple linear regression. The study results show that the organizational commitment component affects job satisfaction by 68.7%, the remaining 31.3% is influenced by other factors not examined. The study results recommend that the leadership pay more attention to increasing employee commitment so that employee job satisfaction can fulfill. Keywords: Organizational Commitment, Employee Job Satisfaction.